"It's Took Over This Region": Patient Perspectives of Prescription Drug Abuse in Appalachia. (1st January 2020) - Mathis, Stephanie M.; Hagemeier, Nicholas; Foster, Kelly N.; Baker, Katie; Pack, Robert P.
Abstract: Background: Prescription drug abuse is a public health problem in the United States and the region of Appalachia, specifically. Primary care and addiction medicine—as possible points of access for prescription drugs with abuse potential and points of intervention for prescription drug abuse—are among the medical fields at its forefront. Little is known, however, about perceptions of prescription drug abuse across the two patient populations. Objectives: The objective of this qualitative analysis was to explore perceptions of the scale and context of prescription drug abuse among primary care and addiction medicine patients in Appalachia. Methods: As part of a mixed methods study, semi-structured interviews were conducted with 20 patients from primary care and addiction medicine in Central and South Central Appalachia from 2014 to 2015. The interviews were audio-recorded and transcribed verbatim. Thematic analysis was used to identify themes. Results : Three themes were identified: (1) pervasiveness of prescription drug abuse, describing perceptions of its high prevalence and negative consequences; (2) routes and routine practices for prescription drug acquisition and distribution, describing perceptions of routes of access to prescription drugs and behaviors exhibited to acquire and distribute prescription drugs; and (3) rationales for prescription drug acquisition and distribution, describing perceptions of the two underlying reasons for these processes—tolerance/addiction and revenue source. Conclusions/Importance : Perceptions of prescription drug abuse among primary care and addiction medicine patients in Appalachia are multifaceted, especially regarding prescription drug acquisition and distribution. Clinical practice implications for mitigating prescription drug abuse are discussed.